Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Budaya Organisasi Terhadap Intention to Stay pada Karyawan Generasi Z (Studi Kasus: Kecamatan Johan Pahlawan, Kabupaten Aceh Barat) - Ana Munawarah; Tamitha Intassar Husen; Desi Yuliana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of job satisfaction, work environment, and organizational culture on the intention to stay among Generation Z employees in Johan Pahlawan Subdistrict, West Aceh Barat. This is a quantitative study of an associative nature. The population in this study consists of employees who belong to Generation Z.. The sampling technique used was purposive sampling, with a sample size of 96 respondents. Data collection was conducted through the distribution of questionnaires using a Likert scale. The data analysis method employed was multiple linear regression analysis using the SPSS program. The results indicate that, individually, the variables of job satisfaction, work environment, and organizational culture have a positive and significant effect on the intention to stay among Generation Z employees. Collectively, job satisfaction, work environment, and organizational culture also have a positive and significant effect on the intention to stay. It is hoped that these findings will contribute to organizations’ efforts to retain their employees, particularly those from Generation Z